Artisanal and Small-Scale Gold Mining in Senegal: Livelihoods, Customary Authority, and Formalization. Issue 8 (3rd August 2017) - Persaud, Anthony W.; Telmer, Kevin H.; Costa, Maycira; Moore, Michele-Lee
ABSTRACT: In Sub-Saharan Africa, efforts to formalize the artisanal and small-scale gold mining (ASGM) sector under legal frameworks and to improve its environmental and health practices have largely failed as a result of top-down policy measures that make change complicated and burdensome for low-resource miners. Using evidence from a case study of the ASGM sector within areas of Senegal, this article demonstrates that ASGM has become an important source of income for many traditionally agricultural rural populations. The findings point toward the embedded nature of ASGM within customary management structures in Senegal, and demonstrate that customary authority is an important component of ASGM operations and development, and should be recognized and integrated into innovative formalization policies and better practices initiatives.